A novel linear 3-O-methylated galactan isolated from Cantharellus cibarius activates macrophages. (15th June 2019) - Yang, Guang; Qu, Yunhe; Meng, Yue; Wang, Yushi; Song, Chengcheng; Cheng, Hairong; Li, Xiaomeng; Sun, Lin; Zhou, Yifa
Highlights: A novel linear 3- O -methylated galactan (WCCP-N-b) from C. cibarius was identified. WCCP-N-b increased phagocytosis and secretion of NO, TNF-α, IL-6 and IL-1β. WCCP-N-b activated macrophages through Akt/NF-κB, MAPKs via TLR2 receptor. The molecular weight of WCCP-N-b impacted the activation. Abstract: A novel polysaccharide (WCCP-N-b) with a molecular weight of 18 kDa was isolated and purified from the fruiting bodies of Cantharellus cibarius . Monosaccharide composition, methylation analysis and NMR spectra indicated that WCCP-N-b was a linear α-1, 6-galactan, partially methylated at O-3 of galactose. The molar ratio of Gal, 3-methylated-Gal, Glc and Man was 14.4:4.6:1.0:1.2. WCCP-N-b could significantly increase macrophage phagocytosis, release of NO and secretion of TNF-α, IL-6 and IL-1β. On a cellular mechanistic level, WCCP-N-b activated MAPKs and NF-κB signaling pathway via Toll-like receptor 2 (TLR2). To further elucidate the structure-function relationship, WCCP-N-b was hydrolyzed by acid. Four degraded fragments were obtained, with molecular weights of 16.1 kDa, 11.2 kDa, 5 kDa and 3.5 kDa, respectively. Their macrophage activation effects were significantly decreased along with the molecular weight decrease. Collectively, WCCP-N-b could activate RAW264.7 cells, and the activation effect was related to its molecular weight.